SPECIES COMPOSITION AND LENGTH-WEIGHT RELATIONSHIP OF ANGUILLID EELS HABITED IN BENGKULU WATERS, INDONESIA - Komang Suryati; Fauziyah Fauziyah; Ngudiantoro Ngudiantoro (Research Centre of Inorganic Materials and Complexs, 2018)
Management of euryhaline species, such as Anguillid eel, is very important. Anguillid eel is an important economic fish which the partly of its life cycle spent in inland waters then migrates into the ocean for spawning. The objective of this study is to identify the morphological diversity and length-weight relationship of Anguillid eels in this province. The total of 148 individuals of elver and adult Anguillid eels were caught was identified using the comparison of ano-dorsal with total length parameter. Cluster analysis was obtained based on measurement of morphometric parameter. The current work used cluster analysis and dendrogram to group the population characteristic of Anguilla eel. It revealed that in the Jenggalu, Kungkai and Manna rivers of Bengkulu province, there are two groups of Anguilla eel with significant difference of ano-dorsal length. The value of the ano-dorsal varied from 2.56 ± 1.54 and 17.78 ± 1.33 for A.bicolor bicolor and A.marmorata, respectively. The length-weight relationships between total length (TL) and weight (W) for Anguilla bicolor and A.marmorata were found to be highly significant (r2 > 0.94, p < 0.001). The average value of 'b' for length and weight were higher than 3, i.e., 3.2677 and 3.4821 in A.bicolor and A.marmorata respectively which indicated a positive allometric growth trend of this species in the studied area.